2011
DOI: 10.1007/s11096-011-9584-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a computerised decision support system for allergic rhino-conjunctivitis counselling in German pharmacy

Abstract: Pharmacists omitted many questions mandatory to assess whether self-medication is appropriate. Using the newly developed PDSS more than doubled the number of mandatory questions asked. The results suggest that the PDSS is ready for evaluation of its impact in real patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…No studies investigated patient outcomes arising from the decision support intervention. Most studies produced a statistically significant positive effect of CDSS on pharmacist activity, exhibited as improved counselling, improved prescribing and better direct collaboration with prescribers or, indirectly, via patient education …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No studies investigated patient outcomes arising from the decision support intervention. Most studies produced a statistically significant positive effect of CDSS on pharmacist activity, exhibited as improved counselling, improved prescribing and better direct collaboration with prescribers or, indirectly, via patient education …”
Section: Resultsmentioning
confidence: 99%
“…Pharmacist counselling for assessment and treatment for allergic rhinitis was improved through the use of a Web‐based CDSS, with a median seven of nine mandatory guideline questions asked compared with two of nine ( P < 0·001) . Pharmacist–patient interventions were a reduction in chronic high‐dose proton‐pump inhibitors (PPIs) (1·67 active vs. 0·17 control interventions per 100 high‐dose PPI prescriptions) and introduction of an antiplatelet agent for prevention of stroke in diabetic patients (1·74 active vs. 0·91 control interventions per 100 patients, P < 0·001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reading the abstracts, 336 articles were preselected for the evaluation of full text. At the end of the article selection process, 26 articles met the specific inclusion criteria. Figure illustrates the progressive selection of the studies used for this review.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty studies showed the effects of documentation in the working process of dispensing practice and, of these, 23 studies included statistical evidence (Table ). According to the methodological analysis of the studies, no article fully met the STROBE and CONSORT criteria.…”
Section: Resultsmentioning
confidence: 99%